Analisis Strategi Nuklir Korea Utara Pasca Perang Dingin: Pengaruh Proliferasi Nuklir Korea Utara Terhadap Stabilitas Keamanan Asia Timur - Reza Adam (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Studies related to international security that focus on conflict issues, military strategy and nuclear weapons became relevant during the ongoing Cold War. However after the Cold War, issues such as nuclear strategy were no longer a major problem, instead issues like economic, technological, social and human rights became more relevant. Thus, the urgency of describing North Korea’s post-Cold War nuclear strategy and it’s impacts on security stability in East Asia is an interesting discussion. This study aims to describe how North Korea's nuclear strategy post-Cold War and how it affects the security stability of East Asia. Method applied is qualitative with a case study approach which will be anaylzed using the deterrence theory and securit dilemma. The results of the research show that North Korea's post-Cold War nuclear strategy has affected security stability in the East Asia region, which is shown from the responses of Japan, South Korea, and China which experienced a security dilemma from North Korea's nuclear proliferation deterrence. North Korea's post-Cold War nuclear strategy by carrying out nuclear proliferation ultimately created a security dilemma in the East Asian region.